Blue Justice to Counter Threats on Ocean Health - Isnurwanto, Iwan; Rafiqi, Ilham Dwi (Universitas Muhammadiyah Yogyakarta, 2025)
Issues of ocean health have become serious threats due to the possibility of damage and quality deflation in Indonesian oceans. From a national defense Fatohoint of view, issues of Indonesian ocean health can fall into national vulnerability and caution. This paper, furthermore, aims to describe and draw justification for the urgency of values and implementation of blue justice to counter ocean health. Normative legal research was applied by means of qualitative analysis of legislation and conceptual variables. According to the research, threats to ocean health could have negative impacts on marine ecosystems, leading to defects in national economic, socio-cultural, defensive, and security systems. In response to the threats to ocean health, littoral societies, thus far, took part in minimum roles, and their existence was unheeded. To tackle the current problem, blue justice is presented, paying attention not only to ecological sustainability in its practice but also to a strong emphasis on social justice that includes relevant parties involved in the management of oceans. It must include littoral societies and fishermen as their lives are strongly dependent on marine resources, which is already and clearly defined in the legislation. In the implementation of blue justice, governments need simultaneous strategies with systematical, integrated, and sustainable efforts, especially in the prevention of any threats to ocean health. Implementing blue justice properly can lead the nation to a blue economy and ensure that oceans are well-protected for the next generation.